Prevalence of Borrelia burgdorferi sensu latu in rodents from two areas with varying wild ungulate densities in Southern Sweden - Nyman, Jimmy (2017)
On a global scale, zoonotic vector-borne diseases pose an increasing threat towards human health. In Europe, the haemotophagous ectoparasite sheep tick (Ixodes ricinus) acts as a pathogen vector for diseases like tick-borne encephalitis and Lyme disease with increasing annual incidences during the last decades. In 2015, Lyme borreliosis was ranked in the top ten priority group of pathogens to guide resource allocation within the Public Health Agency of Sweden. Borrelia burgdorferi sensu lato (s.l) is the pathogen that causes Lyme disease in humans and animals and is maintained in the wild by a complex multi-species transmission process involving tick vectors and many different vertebrate hosts, including humans as dead-end hosts. In Sweden, the relation between B. burgdorferi s.l. prevalence in rodents and ungulate abundance is unknown. In this study, the prevalence of B. burgdorferi s.l. in rodents (Yellow-necked mouse (Apodemus flavicollis), wood mouse (Apodemus sylvaticus) and bank vole (Myodes glareolus), was evaluated in Gnesta/Nyköping (G/N) and Växjö/Vetlanda (V/V), with varying abundances of wild ungulates as moose (Alces alces), roe deer (Capreolus capreolus), red deer (Cervus elaphus) and fallow deer (Dama dama). Rodent data and ungulate population density data were based on data collected by the National Environmental and Wildlife Monitoring and Assessment program at SLU. Prevalence of B. burgdorferi in rodents were analysed with real-time quantitative polymerase chain reaction. The results show equal B. burgdorferi s.l. prevalence in the two study regions (22%), but between species, M. glareolus showed a significantly higher prevalence (26%) compared to Apodemus spp. (15%). B. burgdorferi s.l.. Overall, the infection probability analysis revealed a higher risk for M. glareolus of getting infected than Apodemus spp. However, when comparing infection probability between species in each region, these same results were found for the V/V area, but were contradictory within the G/N reg. The probability of infection also increased with body mass in rodents. Most importantly, the infection probability analysis revealed that deer species such as roe deer and fallow deer did not significantly influence infection probability in rodents. In conclusion, the dataset for prevalence and infection probability analysis, should have been larger to obtain greater statistical power. Also, the method using external oligonucleotides as standard curve reference, are in need of a scientific evaluation.